2020
DOI: 10.1002/jso.25893
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long‐term survival in patients with hepatic resection of colorectal metastases: Analysis of a Brazilian Cancer Center Cohort

Abstract: Background Hepatic metastases are a major cause of death in patients with colorectal cancer. A comprehensive assessment of the prognostic factors associated with long‐term survival could improve patient selection for surgical approaches and decrease morbidity and futile locoregional treatments. Methods We performed a retrospective analysis of patients who underwent hepatectomy for colorectal liver metastases at a single center from 2000 to 2012. Results To identify factors associated with 5‐ and 10‐year overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Therefore, our study evaluated the prognostic impact of several popular definitions. Some differences between our study and other reports were noted [ 6 , 8 , 9 ]. We found that infective complications and major complications did not affect the short-term or long-term survival of the patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, our study evaluated the prognostic impact of several popular definitions. Some differences between our study and other reports were noted [ 6 , 8 , 9 ]. We found that infective complications and major complications did not affect the short-term or long-term survival of the patients.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of previous studies have shown that postoperative complications can reduce patients' long-term survival and increase the risk of disease recurrence in patients with CRLM [7][8][9][10][11]. However, the postoperative complication criteria to determine survival differ among studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the survival rate of colorectal cancer liver metastasis (CRLM) has increased significantly due to the development of chemotherapeutic agents, targeted drugs and combination therapy (6). However, radical surgery remains the most critical method to achieve long-term survival in CRLM, with 5-year survival rates ranging from 40%-60% (2,4,7,8). The liver margin is an important factor in determining whether radical treatment can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…72 Despite attempts to predict recurrence after resection with the proposed scores and prognostic factors, results are heterogeneous, and foreseeing relapse remains a challenge on an individual case basis. 40,45,73,74 Rehepatectomy (RH) or repeated hepatectomy (third and fourth liver resections) can be performed for resectable hepatic recurrence under circumstances where the remnant liver volume is sufficient and patients remain tolerant to surgery. [75][76][77] In these conditions, the procedure has shown adequate safety, with postoperative complications, mortality, and survival rates similar to those for the primary hepatectomy.…”
Section: Resection For Liver-only Recurrencementioning
confidence: 99%